2022
DOI: 10.3390/mi13101560
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Dose–Response Curve of Exoelectrogens: A Microscale Microbial Fuel Cell Biosensor for Water Toxicity Monitoring

Abstract: Nowadays, the development of real-time water quality monitoring sensors is critical. However, traditional water monitoring technologies, such as enzyme-linked immunosorbent assay (ELISA), liquid chromatography, mass spectroscopy, luminescence screening, surface plasma resonance (SPR), and analysis of living bioindicators, are either time consuming or require expensive equipment and special laboratories. Because of the low cost, self-sustainability, direct current output and real-time response, microbial fuel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Another spike test with a lower concentration of formaldehyde (10 mg L −1 ) carried out with the second biosensor (S2) did not lead to a significant decrease in output voltages ( Figure 6 D). Previous studies have shown that the response of an anode-based MFC toxicity sensor is pronounced at concentrations greater than 50 mg L −1 [ 38 , 39 ], although in another study, a higher sensitivity limit of 0.1 mg L −1 was observed for an MFC operated without carbon source addition [ 40 ]. The initial drop in the voltage of S2 can be attributed to the introduction of air bubbles to the biosensor due to a technical error during the formaldehyde exposure test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another spike test with a lower concentration of formaldehyde (10 mg L −1 ) carried out with the second biosensor (S2) did not lead to a significant decrease in output voltages ( Figure 6 D). Previous studies have shown that the response of an anode-based MFC toxicity sensor is pronounced at concentrations greater than 50 mg L −1 [ 38 , 39 ], although in another study, a higher sensitivity limit of 0.1 mg L −1 was observed for an MFC operated without carbon source addition [ 40 ]. The initial drop in the voltage of S2 can be attributed to the introduction of air bubbles to the biosensor due to a technical error during the formaldehyde exposure test.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this toxicity was detected in the tap water being monitored. source addition [40]. The initial drop in the voltage of S2 can be attributed to the introduction of air bubbles to the biosensor due to a technical error during the formaldehyde exposure test.…”
Section: Detection Of Toxicity Spikes In Tap Watermentioning
confidence: 99%